1988
DOI: 10.1038/bjc.1988.3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of organ selective tumour growth by bloodborne cancer cells

Abstract: Summary The sites of tumour development for 6 rat tumours injected into syngeneic rats via different vascular routes was determined. Xenografts of human tumours were also injected intra-arterially (i.a.) into immunosuppressed rats.Following intravenous (i.v.) In explaining the mechanism of site selectivity by bloodborne metastasis the haemodynamic theory of Ewing (1928) stressed the importance of the mechanics of the circulation whereas the Soil/Seed hypothesis of Paget (1889) emphasized the importance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
2
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 49 publications
3
30
2
1
Order By: Relevance
“…The site selectivity of metastases was thought by Ewing (1928) to be determined by haemodynamic considerations of the arterial blood supply, which could be the case in our observations, as the pleura is more invested with the bronchial arterial supply than the parenchyma (Spencer, 1985). However, the soil/seed hypothesis (Murphy et al, 1988), which emphasises the importance of the microenvironment around the metastatic cell, seems attractive since the metastatic mesothelial cells are preferentially localising at a site from which they originated, the pleura, where they ought to have the best microenvironment for continued growth. Fibrosarcoma cells with a propensity to metastasis to the lung (originally induced by methylcholanthrene) have been shown to grow preferentially on the pleura, although initially they are evenly distributed throughout the lung (Orr et al, 1988).…”
Section: Discussioncontrasting
confidence: 42%
“…The site selectivity of metastases was thought by Ewing (1928) to be determined by haemodynamic considerations of the arterial blood supply, which could be the case in our observations, as the pleura is more invested with the bronchial arterial supply than the parenchyma (Spencer, 1985). However, the soil/seed hypothesis (Murphy et al, 1988), which emphasises the importance of the microenvironment around the metastatic cell, seems attractive since the metastatic mesothelial cells are preferentially localising at a site from which they originated, the pleura, where they ought to have the best microenvironment for continued growth. Fibrosarcoma cells with a propensity to metastasis to the lung (originally induced by methylcholanthrene) have been shown to grow preferentially on the pleura, although initially they are evenly distributed throughout the lung (Orr et al, 1988).…”
Section: Discussioncontrasting
confidence: 42%
“…To express a 'soil effect' numerically as a probability that a single cell will cause a deposit requires that following intracardiac injection, the cells are distributed singly within the tissues. This was shown to be the case for normal tissue by Murphy et al (1986;1988) who found that following intracardiac injection of single cell suspensions, the cells distributed in the organs singly and randomly. Individual cells were far apart and there was no possibility that the tumour formed as the concerted action of several cancer cells.…”
Section: Resultsmentioning
confidence: 85%
“…In the present study, enhancement is largely over when the trauma precedes the tumour injection by 14 days. It is noteworthy that transecting the bowel after the cells have reached the tissue does not cause detectable enhancement of tumour growth, even though tumour cells are known to remain viable for up to 24 h after trapping in tissues (Murphy et al, 1988). Enhanced tumour growth at a healing colonic anastomosis is not restricted to one tumour (MC28) as the OES5 carcinoma also grows at colonic anastomoses.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations